ANALYZING THE RELATIONSHIP BETWEEN FREQUENCY IN USING SOCIAL MEDIA AND THE ANXIETY LEVEL OF BODY SHAMING AND HARASSMENT VICTIMS - Julianto, Agnes Happy; Putra, Mochamad Rasyid Aditya; Rahmatika, Nabila Syahfitri; Widyangga, Pressylia Aluisina Putri; Chamidah, Nur (Universitas Negeri Medan, 2023)
In this sophisticated digital era, humans are easier to connect to everything. Unfortunately, this convenience is often used for things that should not be, such as insulting other people through chatting. This makes cyberbullying rampant, especially body shaming and harassment which cause depression, anxiety, and lack of confidence. The aim of this research is analyzing the relationship between the frequency in using social media and the anxiety level as the impact of body shaming and harassment. The research method used in this research is quantitative research with a correlational method. The results of this study are there is no relationship between the frequency of using social media and the anxiety level for both victims of body shaming and harassment, but if viewed based on the results of the respondents it is found that the possibility of cyberbullying is due to the level of education of the perpetrators, attitudes, and behavior. Advice that can be given is the need of further research on the main factors that cause cyberbullying and advice for readers is to control attitudes and behavior while using social media.